The Influence of Flash Sale and Live Streaming on Impulsive Purchases Mediated by Positive Emotions - Muliani, Ervina; Anggriani, Rini; Yuliana, Ika; Delthan, Stevany Hanalya; Assa’ady, M Chotibul Umam (Lembaga Riset, Publikasi dan Konsultasi JONHARIONO, 2025)
The 4.0 digitalization era increases the number of online transactions, one of the e-commerce platforms used is Shopee. Until the end of 2023, this platform recorded the highest number of visitors and continued to innovate through flash sales and live streaming to encourage impulsive purchases. However, several issues have arisen, such as delays in refunds due to stock update errors during flash sales and lag during live streaming. This study aims to analyze the influence of flash sales and live streaming on impulsive buying mediated by positive emotions. The method used is quantitative with data collection through questionnaires filled out by 100 respondents. Data collection was analyzed using the Smart PLS application. The research results show that flash sales have a positive and significant effect on impulsive buying, live streaming has a positive but not significant effect on impulsive buying, flash sales have a positive and significant effect on positive emotions, live streaming has a positive but not significant effect on positive emotions, positive emotions have a negative and not significant effect on impulsive buying, and neither flash sales nor live streaming successfully mediates the effect on impulsive buying. Based on these findings, Shopee is advised to implement flash sale programs more frequently to elicit positive emotions and impulsive purchases from consumers. Then, the host in live streaming should be more transparent in explaining the offered products so that consumers feel more comfortable and spontaneous in making purchases.